Microbial culture collections as pillars for promoting fungal diversity, conservation and exploitation - Sette, Lara Durães; Pagnocca, Fernando Carlos; Rodrigues, André (Elsevier, 2013)
Fungi are a diverse group of organisms with an overall global number of 1.5 M up to 3.3 M species on Earth. Besides their ecological roles as decomposers, fungi are important in several aspects of applied research. Here, we review how culture collections may promote the knowledge on diversity, conservation and biotechnological exploitation of fungi. The impact of fungi diversity on biotechnological studies is discussed. We point out the major roles of microbial repositories, including fungal preservation, prospecting, identification, authentication and supply. A survey on the World Data Center for Microorganisms (WDCM) powered by the World Federation for Culture Collections and on the Genetic Heritage Management Council (CGEN) database revealed that 46 Brazilian culture collections registered in these databases are dedicate to preserving fungi. Most of these culture collections are located in the Southeast of Brazil. This scenario also demonstrates that Brazil has many collections focused on fungal strains, but the lack of up-to-date information in WDCM as well as of a solid national platform for culture collections registration do not allow accurate assessment of fungal preservation. © 2013 Elsevier Inc. All rights reserved.
Keywords: Biological Resources Centres; Biotechnology; Culture collections; Fungal diversity